Informality and Law - Arce Ortíz, Elmer Guillermo (2004)
The phenomenon of informality in Peru is a complex and multifaceted one, reflecting the limitations of the capitalist system in providing decent and survival-enhancing jobs for citizens. The author postulates that the phenomenon of informal activity can be attributed to two fundamental reasons. The first of these reasons relates to unfavourable economic circumstances that force people to act outside the law. The second reason is the intention to deviate from the law in order to increase income in a particular activity. In this context, the social effects of informality include the exclusion of social rights and social segmentation, which serves to highlight the urgency of public policies that address informality as an integral component of society. It is therefore imperative that social law be adapted to guarantee fundamental rights, thereby promoting social inclusion and combating precarious employment. The Constitution must remain the unifying pillar of the legal system, while the State must work to expand the market and formalise the economy, ensuring that all citizens have access to decent and fair living conditions.